Policies for Persons with Special Needs in Benue State: Implementation Challenges and the Way Forward - Ugo, Elizabeth Aundu (NIU Journal of Humanities; Vol 4 No 1 (2019): KIU Journal of Humanities, Vol. 4 No. 1, March 2019, 2019)
Persons with special needs are a group that is vulnerable to social discrimination. In Nigeria, lack of good governance has impacted negatively on people with special needs. Furthermore, the constitution of the Federal Republic of Nigeria does not contain any provision that addresses disability directly. This paper looks at efforts that have been made so far in addressing the plight of person with disabilities, as regards equal opportunities in the area of education and vocational training. The extent which the National Policy on Education is implemented and the role of the National Human Rights Commission in promoting and protecting the rights of persons with special needs are discussed. Recommendations of how to tackle the challenges faced by persons with special needs and the way forward is given. Keywords: Special needs, disabilities, human rights, policy implementation, education.